Investigation of the Hydrogen Gas Production by Using Solar Energy - Yong, Kherng Shi; Mat Isa, Norasikin (Journal of Automotive Powertrain and Transportation Technology, 2023)
Hydrogen is an energy source that offers both environmental benefits and reliability, making it a promising solution for promoting sustainable growth in various sectors worldwide. As businesses and societies increasingly seek sustainable alternatives, hydrogen has emerged as a key player in the transition to a low-carbon economy based on renewable energy sources. Consequently, hydrogen production holds immense potential for replacing traditional energy sources such as petroleum, natural gas, and non-renewable energy. Various methods can be employed for hydrogen production, including fossil fuel-based processes, nuclear energy, and renewable energy sources. To achieve the goal of zero emissions, the focus has shifted towards utilizing renewable energy, specifically through photovoltaic electrolysis, to generate hydrogen gas. Photovoltaic electrolysis employs solar energy to split water molecules into hydrogen and oxygen. However, the efficiency of this method is currently quite low. Temperature plays a crucial role in increasing the efficiency of water electrolysis, making it an important factor to consider in enhancing hydrogen gas production through photovoltaic electrolysis. Therefore, there is significant value in investigating the impact of temperature on the efficiency of hydrogen gas production in photovoltaic electrolysis. In summary, hydrogen energy production has emerged as a promising solution for sustainable growth, and renewable energy sources such as photovoltaic electrolysis hold great potential for achieving zero emissions. Exploring the influence of temperature on the efficiency of hydrogen gas production in photovoltaic electrolysis is of considerable interest, aiming to improve the overall process and enhance the viability of hydrogen as a sustainable energy source.